Eco-friendly polymer composites: A review of suitable methods for waste management - Cabrera, Flávio C. [UNESP] (Wiley, 2021)
The amount of residues generated by agriculture, industrial, or urban activities continuously increases and, consequently, demands several methods for their correct management. The incorrect disposal can cause, in specific cases, environmental contamination by heavy metals or leaching as well as promote the spread of diseases as insect proliferation. Commonly, landfilling, incinerating, composting, or energy/fuel generation can control the disposal or reuse of residues. Among the methods for the reuse of wastes, the incorporation of residues as fillers in polymer composites has emerged as a distinct field. Some composites can potentially mitigate leaching compounds or improve mechanical, thermal, and acoustic properties. However, these improvements are a challenge to promote the use of waste fillers. Thus, this study aims to provide a state of view regarding a variety of wastes used as fillers in polymer composites and different methods to reach mechanical reinforcement as well as improve thermal conductivity and acoustic attenuation for future researches.
Keywords: aerogel; cellulose; fibers; filler; reinforcement